Financial Strategies of Organizations derived from the Regression Analysis:Case of Balcazar Clinic. - Bocanegra Broca, Aarón Alonso; Hernández Govea, Luis Manuel; Vidal Suárez, José Ramón (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJETIVE: To evaluate the opportunities of applying regression analysis in the formulation of financial strategies in organizations, particularly those dedicated to clinical podiatry. MATERIAL AND METHOD: Field research in the "Balcázar" podiatric clinic to know the economic situation of the business and obtain the necessary financial data by applying the ordinary least squares method to estimate the variables corresponding to each statistical-econometric analysis, and subsequently, a light analysis of viability or financial fluidity. RESULTS: The microenterprise has excellent income in relation to its costs and expenses for the support and growth of the business, generating sufficient profits to start future investment projects without fear of economic waste and enjoyment of the profits themselves. This is demonstrated by performing the estimation tests using confidence intervals after different combinations between minimums, average and maximums of the variables used for each of the four regression models. CONCLUSIONS: The business is highly profitable, given both the experience in the field of the owner of the podiatry clinic and the combination of her extensive client portfolio and constant recommendations about her excellent service.